Bear Feasts in a Land without Wild. Bears: Experiments in Creating Animist Rituals. (16th November 2018) - Harvey, Graham
Abstract : Reception of academic debates about animism have led to an increase in the number of people who self-identify as "animists." Among Pagan animists, one example experiments with a midwinter Bear Feast to embed respect for the larger-than-human world in foodways and rituals. To do so they draw on Indigenous and scholarly sources in processes that might be "indigenizing" in several senses. Sources are drawn into an existing tradition, re-shaping it along more localized and more animistic lines. They also encourage the kind of personhood that is more often encouraged among Indigenous people—i.e. promoting "dividuation" rather than the individualizing of consumer capitalist Modernity. Simultaneously, ceremonies are developed that also draw on / in Indigenous knowledges some mediated by scholars. as well as advancing a post-Protestant, un-Modern re-turn to ritual.